A simple and efficient supramolecular solvent based liquid phase microextraction method for the preconcentration of nickel from dandelion tea samples before FAAS quantification, and the practicality and greenness assessment of developed method - Kartoglu, Bedrihan; Bodur, Suleyman; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ELSEVIER, 2024)
A sensitive, accurate and practical analytical method (supramolecular solvent based liquid phase microextraction - flame atomic absorption spectrometry (SUPRAS-LPME-FAAS) was developed for the determination of nickel in dandelion tea samples. All influential parameters of SUPRAS-LPME were optimized to attain low detection/ quantification limits using a univariate optimization approach. Under the optimum SUPRAS-LPME-FAAS conditions, dynamic range, limit of detection (LOD) and limit of quantification (LOQ) were found to be 25.86-497.64 mu g/kg, 8.20 mu g/kg and 27.35 mu g/kg, respectively. The detection power of FAAS system was augmented as 28-fold with the help of SUPRAS-LPME method. Recovery experiments were performed for the evaluation of the accuracy and the applicability of the SUPRAS-LPME-FAAS method and percent recovery results for the spiked dandelion tea samples were calculated between 86.0 and 131.8 % via matrix matching calibration strategy. Additionally, the practicality and greenness evaluations for the SUPRAS-LPME-FAAS method were carried out using BAGI and AGREEprep software, respectively.
Keywords: Nickel; Supramolecular solvent based liquid phase; extraction; Flame atomic absorption spectrometry; Dandelion tea; Matrix matching calibration strategy; CLOUD POINT EXTRACTION; WATER; SPECTROMETRY; TOXICITY; CADMIUM; COBALT; COPPER; ZINC; LEAD; FOOD; Chemistry